Integrated Metabolomic-Transcriptomic Analysis Reveals Diverse Resource of Functional Ingredients From Persimmon Leaves of Different Varieties - Yu, Xian-Mei; Wang, Jie; Gao, Rui; Gong, Bang-Chu; Ai, Cheng-Xiang (Frontiers in Plant Science, 2022)
Persimmon leaves are used for making persimmon leaf tea or as functional ingredients due to their enrichment in flavonoids, the beneficial mineral contents and favorable flavors contributed by volatile aroma compounds. The varieties/cultivars had significant influence on the quality and flavor of persimmon leaf tea. In this research, the integrated metabolomics-transcriptomic analysis was conducted to investigate the potentials in flavonoid biosynthesis, mineral absorption and degradation of aromatic compounds from tender leaves of ‘Diospyros kaki. HeiShi’ (HS), ‘Diospyros kaki Thunb. Nishimurawase’ (NM) and ‘Diospyros kaki Thunb. TaiFu’ (TF), using rootstock ‘Diospyros Lotus Linn’ (DL) as the control. The metabolomic analysis showed that 382, 391 and 368 metabolites were differentially accumulated in the comparison of DL vs. HS, DL vs. NM and DL vs. TF, respectively, and 229 common metabolites were obtained by comparative analysis. By RNA sequencing, 182,008 unigenes with 652 bp of mean length were annotated, and 2598, 3503 and 3333 DEGs were detected from the comparison of DL vs. HS, DL vs. NM and DL vs. TF, respectively. After GO and KEGG enrichment, 6, 6 and 3 DEGs (with |log2(fold change)| ≥1 simutaneously in the three comparisons) involved in flavonoid biosynthesis, mineral absorption and degradation of aromatic compounds respectively were selected for qRT-PCR validation, and the consistent trends of relative expression level of each DEG with RNA-Seq data were observed. Base on the transcriptomic analysis and qRT-PCR validation, it was observed that the leaves of HS, NM and TF had the greatest level in mineral absorption, flavonoid biosynthesis and degradation of aromatic compounds, respectively. In addition, positive correlationship between the 15 DEGs and their metabolites were observed by the conjoint analysis. Thus, the tender leaves of HS, NM and TF could be recommended for the production of persimmon leaf tea rich in mineral elements, flavonoid and aroma compounds, respectively.